Effect of head position changes on the depth of tracheal intubation in pediatric patients: A prospective, observational study - Zhuang, Peier; Wang, Weikai; Cheng, Minghua (Frontiers in Pediatrics, 2022)
Purpose The purpose of this study was to investigate the effect of changing head position on the endotracheal tube (ETT) depth and to assess the risk of inadvertent extubation and bronchial intubation in pediatric patients. Methods Subjects aged 4–12 years old with orotracheal intubation undergoing elective surgeries were enrolled. After induction, the distances between “the ETT tip and the trachea carina” (T-C) were measured using a Disposcope flexible endoscope in head neutral position, 45° extension and flexion, 60° right and left rotation. The distance of the ETT tip movement relative to the neutral position (ΔT-C) was calculated after changing the head positions. The direction of the ETT tip displacement and the adverse events including endobronchial intubation, accidental tracheal extubation, hoarseness and sore throat were recorded. Results The ETT tip moved toward the carina by 0.5 ± 0.4 cm (P < 0.001) when the head was flexed. After extending the head, the ETT tip moved toward the vocal cord by 0.9 ± 0.4 cm (P < 0.001). Right rotation resulted that the ETT tip moved toward the vocal cord direction by 0.6 ± 0.4 cm (P < 0.001). Moreover, there was no displacement with the head on left rotation (P = 0.126). Subjects with the reinforced ETT had less ETT displacement after changing head position than the taper guard ETT. Conclusion The changes of head position can influence the depth of the ETT especially in head extension. We recommend using the reinforced ETT to reduce the ETT displacement in pediatrics to avoid intubation complications. Clinical trial registration [www.ClinicalTrials.gov], identifier, [ChiCTR2100042648].